THERMOPHYSICAL PROPERTIES AND SOLUBILITY OF CARBON DIOXIDE IN AQUEOUS SOLUTIONS OF STERICALLY HINDERED AMINES - MURSHID, GHULAM (2012)
In the present work, a fundamental study is carried out to systematically investigate the potential application of sterically hindered amines (AMP, AHPD), PZ and Piperazine activated aqueous solutions of (AMP and AHPD) for bulk removal of CO2 from various industrial streams to replace the existing conventional amines i.e. DEA and MEA. For this purpose, initially equilibrium solubility was measured for aqueous solutions of AMP, AHPD and PZ with concentrations of (8.91 to 26.73) wt%, (13 to 25) wt% and (1.74 to 10.35) wt% respectively. The experiments were carried out for a full range of pressure from lower to high pressure conditions i.e. 60 bar and at three industrially important temperatures of 303.15, 313.15, and 333.15 K in order to evaluate the solvents performance for industrial application. It has been observed that solubility of sterically hindered amines and PZ is better than conventional amines and the increase in pressure enhances the absorption capacity. However, at higher temperatures, absorption capacity decreases with increasing temperature.